Application of two inductors with single magnetic core in a two-level current source inverter - Suroso, Suroso; Prasetijo, Hari (Institute of Advanced Engineering and Science, 2025)
Current source inverter (CSI) transforms DC current into a predetermined AC current. In practice, the DC current are acquired by connecting inductors with the DC power source. Common-emitter current source inverter (CE-CSI) is an inverter where the emitter terminals of the insulated gate bipolar transistors (IGBTs) or metal oxide semiconductor field effect transistors (MOSFETs) switches are connected at a common voltage. This inverter requires two non-isolated DC current sources as input power. The two level CE-CSI is the simplest circuit of the CE-CSIs. The circuit was able in simplifying inverter circuits compared to the three-level CE-CSI in case of device number, i.e., diodes, IGBTs/MOSFETs, and gate drive circuits. This paper studied the basic characteristics of the two-level CE-CSI when two reactors with a single magnetic core were used. The inverter circuit was examined and evaluated through computer tests, and experimentally. The two-level CE-CSI was able to generate a low distortion of sinusoidal AC load current with total harmonic distortion (THD) value 1.92%. Test data showed that the magnitudes of low order harmonics were less than 0.3% of the fundamental frequency. Moreover, the inverter efficiency can be increased due to reduction of the power losses caused by power switching devices.